Identification of Lysine Succinylome and Acetylome in the Vancomycin-Intermediate Staphylococcus aureus XN108 - Li Tan; Yi Yang; Weilong Shang; Zhen Hu; Huagang Peng; Shu Li; Xiaomei Hu; Xiancai Rao (Microbiology Spectrum, 2022)
ABSTRACT Protein posttranslational modifications (PTMs) play important roles in regulating numerous biological functions of prokaryotic and eukaryotic organisms. Lysine succinylation (Ksucc) and acetylation (Kac) are two important PTMs that have been identified in various bacterial species. However, the biological functions of Ksucc and Kac in vancomycin-intermediate S. aureus (VISA) remain unclear. In this study, we systematically identified 3,260 Ksucc sites in 799 proteins and 7,935 Kac sites across 1,710 proteins in the VISA strain XN108. Functional analyses revealed that both Ksucc and Kac sites were highly enriched in several critical metabolic pathways, including ribosomal metabolism, tricarboxylic acid cycle, and glycolysis. Furthermore, a remarkable cross talk between Ksucc and Kac modifications was observed that almost 75% of the succinylated sites were also frequently acetylated. In addition, we identified SaCobB, a Sirtuin 2-like lysine deacetylase, as a bifunctional enzyme with both deacetylation and desuccinylation activities in S. aureus. We demonstrated the first lysine succinylome and acetylome in a VISA and identified SaCobB, a functional enzyme taking part in the regulation of Ksucc and Kac in S. aureus. Our findings provide valuable information for further study on the regulatory mechanisms of PTMs in S. aureus. IMPORTANCE Lysine succinylation (Ksucc) and acetylation (Kac) are two important protein posttranslational modifications (PTMs) that regulate numerous biological functions in prokaryotes and eukaryotes. However, the functions of Ksucc and Kac in Staphylococcus aureus are seldom described. Understanding of Ksucc and Kac modifications in S. aureus will facilitate the development of new strategies to control infections. Herein, we quantified both Ksucc and Kac in a vancomycin-intermediate S. aureus (VISA) strain XN108, analyzed the interaction between these two PTMs, and identified SaCobB as a bifunctional enzyme with both deacetylation and desuccinylation activities. This study is the first description of dual PTMs, Ksucc and Kac profiles, in the VISA. The findings could provide valuable information for the following researches on the regulatory roles of PTMs in S. aureus.